INFORMATION TECHNOLOGY GOVERNANCE IN A SHARIA MICROFINANCE INSTITUTION: AN EVALUATION BASED ON COBIT 5 FRAMEWORK - Zayyinatul Khusna; Syaiful Ali (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2020)
This research aimed to analyze the implementation of Information Technology (IT) management and to measure the level of IT management in Bina Ummat Sejahtera KSPPS BMT (Saving-Loan Cooperation and Sharia Financial Baitul Maal Wat Tamwil) using the COBIT framework 5. Bina Ummat Sejahtera KSPPS BMT is one of the Sharia Micro Finance Institutions in Central Java. The process capability model in COBIT 5 was used to measure the level of IT management in Bina Ummat Sejahtera KSPPS BMT. This research applied a qualitative approach using interviews and documentation to collect data. The results show that Bina Ummat Sejahtera KSPPS BMT has implemented the management process and met all the process domains in the COBIT 5 framework. Also, the level of IT governance at Bina Ummat Sejahtera KSPPS BMT is currently at level 3 (established process), the defined process level. Overall, the management process can only reach the level of